Post-transcriptional Gene Regulation in Colitis Associated Cancer - Chen, Gang; Feng, Yuan; Li, Xuezheng; Jiang, Zhe; Bei, Bei; Zhang, Lin; Han, Yueqing; Li, Yanwu; Li, Ning (Frontiers in Genetics, 2019)
Colitis-associated cancer (CAC) has been linked to microRNA (miRNA) aberrant expression elicited by inflammation. In this study, we used the AOM/DSS-induced CAC mice model to explore the miRNAs that were aberrantly expressed. As a result, we found that miR-31-5p, miR-223-3p, and let-7f-5p were dysregulated during the intestinal atypical hyperplasia. Subsequently, we first identified the role of these three miRNAs in CAC. Adenomatous polyposis coli (APC) was revealed a new target of miR-223-3p, while solute carrier family 9- subfamily A-member 9 (SLC9A9) and APC membrane recruitment protein 3 (AMER3) were two new targets for let-7f-5p. For miR-31-5p, we proved that it can target LATS2 mRNA so as to modulate Hippo pathway in Caco2 cells. Second, to examine if targeting these three miRNAs would lead to the CAC preventive, pedunculoside, a natural triterpene glycoside which was found to be able to rescue the down-regulation of LATS2 and APC by either miR-31-5p or miR-223-3p overexpression, respectively, was used in the in vivo AOM/DSS-induced CAC model. The results showed that pedunculoside (25 mg/kg) substantially mitigated the damage on mice intestine caused by DSS/AOM. These results suggested that miRNAs-elicited post-transcriptional regulation is involved in the pathogenesis of CAC, and CAC can be prevented through targeting key miRNAs that are ectopically expressed in CAC.